DEVELOPMENT OF ELECTRONIC TEACHING MATERIALS BASED ON ENRICHED VIRTUAL MODEL ON HUMAN RESPIRATORY SYSTEM MATERIALS TO IMPROVE STUDENT'S COGNITIVE ABILITY - Nurmila Ichsan; Djuna Lamondo; Masra Latjompoh (Universitas Negeri Medan, 2022)
This study aims to produce electronic teaching materials based on blended learning enriched virtual models that are valid, practical, and effective in improving students' cognitive abilities. This type of research is Research and Development (R&D). The subjects in this study were 15 students of class VIII junior high school. Two expert validators and one practitioner carry out validation to assess the product from the aspects of presentation, content, and language. Practicality is assessed based on the implementation of learning, student activities, and student responses to electronic teaching materials. Effectiveness is assessed based on THB. The study results obtained: (1) The design of electronic teaching material products discusses the structure and function of the organs of the human respiratory system equipped with images, audio, and video. (2) The validation of these electronic teaching materials obtained an average score of 93% (very valid). (3) The practicality test score from the learning implementation results obtained 100% (very good), the student activity score was 89.5% (very good), and the student response results obtained 95% (very good). (4) The effectiveness test results based on N-Gain analysis obtained an average score of 0.7 medium criteria. Thus, the electronic teaching materials developed are suitable for learning support to improve students' cognitive abilities in the human respiratory system material. The research implies that it can be of information for broader research.